THE EFFECT OF SERVICE QUALITY, DESTINATION IMAGE, AND MEMORABLE EXPERINCE ON REVISIT ITENTION OF CAMPX JATILUHUR - Monica, Yolanda; Rodhiah, Rodhiah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to determine the effect of service quality, destination image, and memorable experience on the intention to revisit the CampX Jatiluhur tour. The population of this study were all visitors to Campx Jatiluhur, while the technique used in sampling was purposive sampling with a sample of 100 respondents. This analysis process uses the SEM method and will be processed with SmartPLS 4 software with 2 elements of the PLS path model, namely inner model analysis and outer model analysis. Based on the results of the study, it can be concluded that Service Quality has a positive and significant effect on the intention to revisit CampX Jatiluhur tourism, Destination Image has a positive and significant effect on the intention to revisit CampX Jatiluhur tourism, and Memorable Experience has a positive and significant effect on the intention to revisit CampX Jatiluhur tourism.